Post‐Fire Comparisons of Forest Floor and Soil Carbon, Nitrogen, and Mercury Pools with Fire Severity Indices. Issue Volume 78:Issue Supplement 1(2014) (20th June 2014) - Kolka, Randy; Sturtevant, Brian; Townsend, Phil; Miesel, Jessica; Wolter, Peter; Fraver, Shawn; DeSutter, Tom
Abstract : Forest fires are important contributors of C, N, and Hg to the atmosphere. In the fall of 2011, a large wildfire occurred in northern Minnesota and we were able to quickly access the area to sample the forest floor and mineral soil for C, N, and Hg pools. When compared with unburned reference soils, the mean loss of C resulting from fire in the forest floor and the upper 20 cm of mineral soil was 19.3 Mg ha −1, for N the mean loss was 0.17 Mg ha −1, and for Hg the mean loss was 9.3 g ha −1 . To assess the influence of fire severity on the forest floor and mineral soils, we used an established method that included a soil burn severity index and a tree burn severity index with a gradient of severity classes. It was apparent that the unburned reference class had greater forest floor C, N, and Hg pools and higher C/N ratios than the burned classes. The C/N ratios of the 0‐ to 10‐ and 10‐ to 20‐cm mineral soils in the unburned reference class were also greater than in the burned classes, indicating that a small amount of C was lost and/or N was gained, potentially through leaching unburned forest floor material. However, with a couple of exceptions, the severity classes were unable to differentiate the forest floor and mineral soil impacts among soil burn and tree burn severity indices. Developing burn severity indices that are reflective of soil elemental impacts is an important first step in scaling ecosystem impacts both within and across fire events.